Hayahay medical resort for orthopedic and sports medicine in Dumaguete City - Udtohan, Miel Adonis L.
The purpose of this study is to design a globally competitive healthcare facility that caters to local sports athletes. A facility that will act as a support facility together with the existing athletics program to promote athletes to the local population, in the hopes of one day aid raising the athlete standards in the country. Integrating this facility with a resort environment, and with Dumaguete becoming a major tourism jump-off point, the development is also projected to become a key player in boosting the region's medical tourism industry by securing a health service niche on Orthopedics and Sports Medicine, that will attract not only local medical tourists, but also expats, and foreigners who are looking for the right package of wellness and recreation. This study may be useful as basis in developing a standard for medical tourism institutions that can not only provide quality medical services to the country's citizenry, but also to become a prime choice of foreigners and tourists for any of their health and wellness needs.